Using Optimization Technique, Friction Welding Process Parameters Are Experimentally Evaluated and Optimized On Identical Materials - Anil Kumar; Mr. Vikash Ganpale (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
In fabrication industry, joining processes play a very important role. Among various joining processes, welding process has more strength as compared to other joining processes. Friction welding is a solid state welding, which is used to join similar or dissimilar materials by applying pressure and without the need of filler materials for heat production. Also, friction welded joints can produce welds that are superior in strength of the parent material. Friction welding enables similar or dissimilar materials to be joined together by sliding one material against the other under pressure. Friction welding process includes upset time, upset pressure, and heating time, heating pressure and rotating speed. In this experimental work, friction joints are carried out by centre lathe machine. In this experimental work, metal joining were made by using centre lathe machine, welding of similar materials are done using the input process parameters like spindle speed, heating pressure, upset time, upset pressure, heating time, material to be welded, component size and configuration based on the literature review. Then the welded joints are tested to study and analyse the mechanical properties like axial shortening, hardness and impact strength to get the improved quality of welded joints and to optimize the process parameters using Taguchi method. Ranking is generated for the various combinations of input process parameters like upset time, upset pressure, heating time and heating pressure by using a multi-objective optimization technique like Grey Relational Analysis (GRA). The friction welding of similar Aluminium alloy Al6061 using centre lathe machine and find the optimal level of input parameters to improve the mechanical properties like axial shortening, hardness, impact strength are identified and presented in this work using DoE and GRA rankings.
Keywords: Upset time; Upset pressure; Rotating speed; Spindle speed; Hardness; Grey Relational Analysis; Tension test